Exploring children's play in early years learning environments; what are the factors that shape children's play in the classroom?. (September 2019) - Kinkead-Clark, Zoyah
In the Caribbean, as with many other contexts, though learning through play serves as the impetus behind recommended early years classroom practices, very little is known about children's play, what it looks like and the factors that shape it. To explore this issue, traditional qualitative methodology including interviews, documentation of field notes, and observations of three early years classrooms for children aged 4 years was done. Thematic analysis of the data revealed five overarching themes: (1) revealing conversations, (2) leaders take charge, (3) gender roles, (4) teachers' practices and (5) availability of resources. The findings highlight the revealing conversations, social hierarchies and stereotypical gender roles evident in children's play. Likewise, children's play is also shaped by teachers' practices and the availability of resources. The research findings speak to complex nature of children's play. In this, play serves as a means to demonstrate leadership qualities and share stories about themselves. This highlights the necessity of play as not only benefitting children physically, but socio-emotionally and cognitively as well. Of note as well is that though beneficial, there are also obstacles which impact children's play, teachers' practices and the availability of resources. Though these findings cannot be used to make wholesale assumptions about what is happening in all early childhood classrooms, it does draw attention to how teachers implement play-based curricula. Likewise it points to the need to examine how barriers to play minimise children's ability to positively gain from plethoric benefits play has to offer.